Kwestia wiary w jednego Boga w perspektywie ksiąg pokutnych i przygotowania do spowiedzi furtkowej - Nawracała, Tomasz (Uniwersytet im. Adama Mickiewicza w Poznaniu. Wydział Teologiczny, 2016)
The ideal Christian life is expressed in the sentence: to be holy because God is holy. Achieving such holiness is only possible in cooperation with God’s grace, which heals and relieves human weaknesses and sins. The way to holiness leads through confession, in which man receives the forgiveness of sins. In recent years in Poland, the practice of the so-called ‘gateway confession’ has developed. This confession focuses mainly on the first commandment of the Decalogue and greatly suppresses all the others. In the present article we show an approach to confession in the perspective of the practice of gateway confession and preserved recommendations from medieval penitential books. The two approaches are different but – ultimately – both refer to the Decalogue selectively.
The question of faith in one God in the perspective of penitential books and preparation to gateway confession
Keywords: spowiedź; grzech; wiara; Bóg; Komunia Święta; Libri poenitentiales; confession; sin; faith; God; Holy Communion